Implementasi Bimbingan Moralitas Yayasan Rumah Impian Indonesia dalam Meningkatkan Resiliensi Anak Jalanan di Yogyakarta - Qotimah, Alda Nurul; Hakim, Lukman (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to explore the implementation of moral guidance carried out by the Indonesian Dream House Foundation in increasing the resilience of street children. Dream House empowers street children to transform into independent and caring individuals. One effort to improve morality in street children is through the presence of the Indonesian Dream House Foundation as an educational forum, especially in the field of street morals. This study is a study with a descriptive qualitative approach. Data collection techniques through observation, documentation, and in-depth interviews with six (6) foster children and one (1) foundation administrator. The results of this study indicate that the Yogyakarta Dream House Foundation provides maximum moral guidance to foster children and has a positive impact felt by street children by including increasing morality and resilience as seen from their emotional and social development, foster children show diverse hopes and ideals, which reflect their aspirations for a better future.
Keywords: Street Children; Morality; Educatiin; Resilience; Yayasan Rumah Impian